Modelling and evaluation of "Fixed Horizon", "Rolling Horizon" and "Real Time Management" production scheduling paradigms in ubiquitous production networks under conditions of dynamic environments for economic and environmental sustainability - Alves, Cátia Filipa Veiga (2017)
Doctoral Degree in Industrial and Systems Engineering